Pengembangan Media Belajar Flash Card dalam Pembelajaran IPS Kelas VII MTS Darussalam Aryojeding Tulungagung - Mahila Zahra; Hendra Pratama (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research was motivated by the lack of students’ interest in Social Studies (IPS) learning. Grade VII students often experience difficulties in understanding and remembering Social Studies material. The aim of this study is to determine the effectiveness of using flash card learning media for Social Studies learning in Grade VII at MTs Darussalam Aryojeding Tulungagung. The type of research used is Research and Development (R&D), employing the Borg and Gall development model. The flash card learning media developed in this study were validated by subject matter experts, media experts, and Social Studies teachers. The research subjects were 26 students of Grade VII B at MTs Darussalam Aryojeding Tulungagung. The results of the validity tests showed a score of 83% from the subject matter expert, 86% from the media expert, and 85% from the teacher. The effectiveness test of the media product using the Paired Sample T-test showed a significance value of 0.000, which is lower than the 0.05 threshold, indicating that the alternative hypothesis is accepted. This demonstrates that there is a significant difference in student learning outcomes before and after using the flash card learning media. In conclusion, this study confirms that the flash card learning media on the topic of environmental pollution for Grade VII B at MTs Darussalam Aryojeding Tulungagung is considered valid by experts and effective in improving student learning outcomes.